2020
DOI: 10.1101/2020.01.20.912352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barley shoot biomass responds strongly to N:P stoichiometry and intraspecific competition, whereas roots only alter their foraging

Abstract: 1 Background and Aims Plants respond to various environmental stimuli, and root systems 2 are highly responsive to the availability and distribution of nutrients in the soil. Root system 3 responses to the limitation of either nitrogen (N) or phosphorus (P) are well documented, 4 but how the early root system responds to (co-) limitation of one (N or P) or both (N and 5 P) in a stoichiometric framework is not well known despite its relevance in agriculture. In 6 addition, how plant-plant competition (here int… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…In view of the root economics spectrum (Ma et al, 2018; Valverde‐Barrantes et al, 2015), the decrease in root diameter may increase the efficiency of root growth and thus enhance root length to explore temporal and spatial available resources (Kuzyakov & Xu, 2013; Ma et al, 2018; Wen, Li, Shen, & Rengel, 2017). Accordingly, specific root length increased with belowground intraspecific competition (RCI of roots) and increasing planting densities (Figure S2b), which is in agreement with previous studies (Kumar et al, 2020; Li et al, 2019). Furthermore, soil C and N turnover were modulated by root morphological traits at higher planting densities, since both SOM‐C and N mineralization increased with specific root length for the double and triple densities (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…In view of the root economics spectrum (Ma et al, 2018; Valverde‐Barrantes et al, 2015), the decrease in root diameter may increase the efficiency of root growth and thus enhance root length to explore temporal and spatial available resources (Kuzyakov & Xu, 2013; Ma et al, 2018; Wen, Li, Shen, & Rengel, 2017). Accordingly, specific root length increased with belowground intraspecific competition (RCI of roots) and increasing planting densities (Figure S2b), which is in agreement with previous studies (Kumar et al, 2020; Li et al, 2019). Furthermore, soil C and N turnover were modulated by root morphological traits at higher planting densities, since both SOM‐C and N mineralization increased with specific root length for the double and triple densities (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…Root hairs are known to be essential for acquiring P because P is highly immobile in the soil due to adsorption and precipitation, and uptake by bulk flow and diffusion is very low (Gahoonia et al, 1997; Haling et al, 2013). By altering N and P availability in a stoichiometric manner, Kumar et al (2020) showed that barley had greater proportion of root biomass in deeper soil layers when N was the limiting nutrient and the reverse root response was true for P limitation. In our study, we found no effect of N and P fertilization timing on RMF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, morphological and root system architecture (RSA) responses, such as an increase in lateral root length over the amount of laterals, increase in lateral root elongation steeper and angle of laterals, and an increase in root hair length/density are all common plant responses as a mean to increase P uptake when it is limiting (Haling et al, 2013; Linkohr et al, 2002). In contrast to P‐limited plants, N‐limited plants tend to invest more roots in deeper layers because N (especially in the form of NO 3 − ions) is more mobile in soil than P, and they achieve this by changing root growth angles—a root architectural response (Kumar et al, 2020; Trachsel et al, 2013). Consequently, breeding for these specific adaptations in crops could prove advantageous for productivity in N‐ and P‐deficient soils (Lynch, 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we believe that plastic and species-specific root responses to plant order of arrival are more likely to explain why grasses-first communities rooted more shallowly than the others did. Such plastic root responses affecting root allocation and foraging have been well documented in the past (Mahall and Callaway, 1991;Semchenko et al, 2007;Mommer et al, 2012;Kumar et al, 2020;Lepik et al, 2021) but, to date, there has been little evidence that the order of arrival of plants can affect the root distribution of individual species (Weidlich et al, 2018a). Studying the extent to which the behaviour of the roots of species inhabiting plant communities changes as a function of the order of arrival of plants, as well as studying how these plastic root responses would be reflected at the community level, requires information on the distribution of roots at the species level, which unfortunately was not available in our study.…”
Section: Discussionmentioning
confidence: 93%